2017
DOI: 10.1002/mgg3.360
|View full text |Cite
|
Sign up to set email alerts
|

Patients with sporadic and familial amyotrophic lateral sclerosis found value in genetic testing

Abstract: BackgroundAmyotrophic lateral sclerosis (ALS) is increasingly recognized as a genetic disease. There is no consensus, however, as to the role of genetic testing in the care of the ALS patient.MethodsWe conducted a survey to study patient access, attitudes, and experience with ALS genetic testing among patients enrolled in a US ALS registry.ResultsAmong 449 survey respondents, 156 (34.7%) were offered testing and 105 of 156 (67.3%) completed testing. The majority of respondents with familial ALS (fALS) (31/45, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 17 publications
0
34
0
1
Order By: Relevance
“…The survey gathered information regarding genetic testing and counselling practices, as well as clinician attitudes and other factors that may be associated with the offer of genetic testing. In addition, we compared clinician attitudes towards genetic testing to attitudes of persons with ALS, which we have previously reported (7). The findings of this study may inform the development of consensus practice guidelines for ALS genetic testing and counselling, which may in turn enable more consistent patient access to genetic information, risk assessment, and, in the future, targeted treatment options for persons with ALS.…”
Section: Introductionmentioning
confidence: 93%
“…The survey gathered information regarding genetic testing and counselling practices, as well as clinician attitudes and other factors that may be associated with the offer of genetic testing. In addition, we compared clinician attitudes towards genetic testing to attitudes of persons with ALS, which we have previously reported (7). The findings of this study may inform the development of consensus practice guidelines for ALS genetic testing and counselling, which may in turn enable more consistent patient access to genetic information, risk assessment, and, in the future, targeted treatment options for persons with ALS.…”
Section: Introductionmentioning
confidence: 93%
“…Among those who had testing, those who received positive and negative results reported equally favorable experiences, suggesting that those who get "bad news" maintained a favorable outlook about the benefits of testing. 18,19 Attitudes toward presymptomatic ALS testing have also been studied; in a study of family members of persons with ALS, 60% indicated they would have presymptomatic testing if offered. 20 Challenges in Laboratory Detection and Interpretation of the HRE PCR-based assays for detection of the HRE are widely used in commercial laboratories, but their accuracy has been questioned.…”
Section: Current Status Of Testing and Counselingmentioning
confidence: 99%
“…Indeed, a genetic cause in seemingly sporadic ALS can be masked by recessive inheritance, reduced penetrance, small family size, lack of family information, and illegitimacy. Within the last few years, neurologists started offering genetic counseling to ALS patients more frequently and patients who underwent genetic counseling reported a positive experience and found value in testing [ 41 ]. According to the guidelines of the German Society of Neurology, genetic testing should be offered to patients with familial ALS, patients who have family members with dementia, and patients with an early onset and rapid progression [ 28 ].…”
Section: Genetic Testing and Counselingmentioning
confidence: 99%